Development Evaluation in PEO and Its Impact Volume II - Planning Commission (Planning Commission, 2006)
Ever since the concept of planning was introduced in India, the task pertaining to formulation of improved plan and design for the development schemes and programmes for effective implementation in a given situation with varied geo-climatic conditions on the one hand and diverse socio-economic characteristics of the Indian states on the other had always posed a great challenge before the planners and policy makers. However, the founding fathers of Programme Evaluation Organisation (PEO) had a visionary objective that aimed at envisaging a crucial role for the Organization in bringing out objective and credible evaluation results concerning the grassroots reality which would be used in the plan formulation and improving the service delivery.
Programme Evaluation Organisation Planning Commission Government of India
Programme Evaluation Organisation Planning Commission Government of India